Squeeze-out w anonim şirket (tureckiej spółce akcyjnej) - wybrane aspekty - Delczyk, Dominik (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The article is about the squeeze-out right in Turkish company - anonim şirket. Despite some similarities, the Turkish model of squeeze-out is significantly different from the squeeze-out regulations which are in force in most countries. Its originality results from the specificity of economic conditions and axiology, according to which property rights deserve special legal protection. Some of the solutions adopted in Turkish law are innovative and may inspire lawmakers also in other countries. The paper includes analysis of the legal norms which are in force in the Republic of Turkey. The research was conducted based on the views presented by representatives of the doctrine.
Keywords: squeeze-out; turkish law